Development of coordination abilities in children aged 9-10 years with a diagnosis of myopia (Bangladesh Journal of Medical Science, 2024)
Objective The objective is to increase the level of coordination abilities of schoolchildren diagnosed with myopia.Methods The study was conducted in the period from September 2022 to June 2023 at secondary school number 13 in the Kirov region. A group (n=21) of 4th grade students was formed to conduct a pedagogical experiment. These are boys and girls aged 10-11 years with a mild degree of myopia (up to 3 diopters) – myopia of the first degree. The level of development of coordination abilities was determined by a 3x10 meter Shuttle run, a long jump from a place with the right and left sides, Balance on 1 leg and Dynamic coordination of movements. The Student’s T-Test was the main method of mathematical statistics.Results After the end of the pedagogical experiment, the performance of children from the experimental group improved in all indicators. In the shuttle run test, the indicators became higher from 9.36±0.16 to 8.72±0.09 (p